1997
DOI: 10.1111/j.1749-6632.1997.tb52355.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Observed Relationship between Low Cholesterol and Violence‐related Mortality

Abstract: Health advocacy groups advise all Americans to restrict their dietary intake of saturated fat and cholesterol as an efficacious and safe way to lower plasma cholesterol concentrations and thus reduce the risk of coronary heart disease and other atherosclerotic disorders. However, accumulating evidence suggests that naturally low or clinically reduced cholesterol is associated with increased nonillness mortality (principally suicide and accidents). Other evidence suggests that such increases in suicide and trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 101 publications
2
32
0
9
Order By: Relevance
“…In experiments using nonhuman primates, animals assigned to cholesterol-lowering diets acted more aggressively and exhibited less affiliative behavior than those on a high-fat diet. 42 The current study suggests that statin drugs may increase aggression.…”
Section: Discussionmentioning
confidence: 65%
“…In experiments using nonhuman primates, animals assigned to cholesterol-lowering diets acted more aggressively and exhibited less affiliative behavior than those on a high-fat diet. 42 The current study suggests that statin drugs may increase aggression.…”
Section: Discussionmentioning
confidence: 65%
“…Although other studies have suggested that serum cholesterol may be a marker for central serotonergic activity (Steegmans et al, 1996;Terao et al, 2000;Vevera et al, 2005), it is worth noting that Hibbeln et al (1998) found a strong correlation between brain serotonin metabolites and omega-3 fatty acids, a finding suggesting that, in previous studies, cholesterol was acting as a ''surrogate marker'' for omega-3 fatty acids (Hibbeln et al, 2000). Kaplan et al (1997) proposed a plausible evolutionary rationale for the cholesterol-serotonin hypothesis. They argue that, rather than being an accidental relation, natural selection may have shaped the behavioral and physiological responses induced by a reduction in serum cholesterol to provide an adaptive advantage.…”
Section: Neural Mechanismsmentioning
confidence: 93%
“…Food deprivation, hunger and their effects on violent mechanisms are public concerns and issues that need to be studied more. Derleme / Review GİRİŞ Besin öğesi yetersizliklerinin bireylerin ruhsal durumunu etkilediği çeşitli çalışmalarla gösterilmiştir (1)(2)(3)(4)(5). Saldırganlık ve şiddet içeren, kendine ve başkasına zarar verici davranış-larda bulunan bireylerde bazı besin öğelerinin eksiklikleri veya nörotransmitterlerin metabolizmasındaki bozuklukların rolü olabileceği görüşü yaygındır.…”
Section: Hunger and Violenceunclassified
“…Düşük kolesterol düzeyinin serotonin fonksiyonunu etkilediği ileri sürülmektedir. Düşük kolesterollü diyetle beslenen maymunların, yüksek kolesterol diyeti ile beslenenlere oranla BOS'da serotonin düzeyleri düşük bulunmuştur (4). Başka bir çalışmada, majör depresif, şizof-ren grup ve kontrol grubu karşılaştırılmış, şizofreni grubunda toplam kolesterol düzeyleri majör depresyon grubuna göre anlamlı ölçüde düşük bulunmuş, majör depresyon grubuyla sağlıklı kontroller arasında toplam kolesterol düzeyi açısından fark bulunmamıştır.…”
Section: Yağ Asitleri Yetersizliklerinin Davranışlara Etkileriunclassified